Development of a bacterial artificial chromosome (BAC) recombineering procedure using galK-untranslated region (UTR) for the mutation of diploid genes - Dai, Gan (2012)
Bacterial artificial chromosome (BAC) recombineering using galK selection allows DNA cloned in E. coli to be modified without introducing an unwanted selectable marker at the modification site. Genomes of some herpesviruses have a pair of inverted repeat sequences that makes it very difficult to introduce mutations into diploid (duplicate) genes using the galK selection method. To mutate diploid genes, we developed a galK-UTR BAC recombineering procedure that blocks one copy of the target diploid gene by insertion of a galK untranslated region (UTR), which enables the simple mutation of the other copy. The blocked copy can then be replaced with a UTR-specific primer pair. The IR2 gene of equine herpesvirus 1 (EHV-1) maps within both the internal (IR) and terminal repeat (TR) of the genomic short region and is expressed at low levels because its promoter is TATA-less. Both IR2 promoters in EHV-1 BAC were replaced with a mutant IR2 promoter containing three Sp1-binding motifs and a consensus TATA box by galK-UTR BAC recombineering. The expression level of the IR2 protein controlled by the modified promoter increased approximately 4-fold as compared to that of wild-type EHV-1. The galK-UTR method will provide a useful tool in studies of herpesviruses.